Nanoparticles in Soil Remediation: Challenges and Opportunities - New, Wei Xuen; Ogbezode, Joseph Ekhebume; Gani, Paran (Tecno Scientifica Publishing, 2023)
Nanoremediation emerges as a promising technology for mitigating soil contamination, encompassing various nanotechnology applications, including chemical degradation, Fenton-type oxidation, photocatalytic degradation, immobilization, and integration with bioremediation techniques like phytoremediation. In addressing soil pollution, the most extensively researched nanomaterials (NMs) are based on carbon, metal and metal oxide, nZVI, and other nanocomposites. Nevertheless, limitations accompany the use of NMs in soil remediation. To assess whether nanotechnology applications outweigh environmental threats, it is crucial to investigate potential effects of NMs on terrestrial vegetation, soil organisms, and human well-being. The impacts of NMs on ecology and the soil environment must be taken into consideration when formulating remediation strategies. Future directions for applied and fundamental studies could include developing multifaceted nanocomposites, integrating them with technologies like bioremediation. Additionally, exploring real-time control and monitoring of NMs and their efficacy in removing pollutants is worth consideration. Pursuing these avenues is vital for advancing the field of soil remediation and comprehending the impact of nanotechnology on the environment.